2020
DOI: 10.21037/atm-20-6620
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing identifies prognostic mutational signatures in gastric cancer

Abstract: Background: Gastric cancer (GC) is a heterogeneous disease, and is a leading cause of cancer deaths in Eastern Asia. Genomic analysis, such as whole-exome sequencing (WES), can help identify key genetic alterations leading to the malignancy and diversity of GC, and may help identify new drug targets.Methods: We identified genomic alterations in a cohort of 38 GC patients, including 26 metastatic and 12 non-metastatic patients. We analyzed the association between novel gene mutations and copy number variations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Pseudogene UBE2MP1 was found to have a significant expression-methylation-correlation difference between normal and cancerous breast tissue [53]. UBE2MP1 was also found to be amplified in gastric cancers with amplified copy number variations in the 16p11.2 region, a mutation found to be associated with shorter overall survival [57], and was predicted to be a driver of lung adenocarcinoma [56].…”
Section: Novel Findings By Tigarmentioning
confidence: 98%
See 2 more Smart Citations
“…Pseudogene UBE2MP1 was found to have a significant expression-methylation-correlation difference between normal and cancerous breast tissue [53]. UBE2MP1 was also found to be amplified in gastric cancers with amplified copy number variations in the 16p11.2 region, a mutation found to be associated with shorter overall survival [57], and was predicted to be a driver of lung adenocarcinoma [56].…”
Section: Novel Findings By Tigarmentioning
confidence: 98%
“…TIGAR identified 3 novel independent TWAS risk genes (KLHL25, UBE2MP1, and FRG1EP ) for breast cancer. Gene KLHL25 has known biological functions involved in carcinogenesis, while genes UBE2MP1 and FRG1EP are near such a gene [53][54][55][56][57].…”
Section: Novel Findings By Tigarmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereditary stomach cancer is associated with mutations in the CDH1 gene and it is also manifested in Lynch (hereditary nonpolyposis colorectal cancer) syndrome related to mutations in mismatch repair genes [45][46][47][48]. Next-generation sequencing studies have identified rare germline variants in several other genes, including BRCA2 and other DNA repair genes [49][50][51]. In kidney cancer, the contribution of von Hippel-Lindau syndrome is a likely explanation for the early onset risk component [52].…”
Section: Genetic Implicationsmentioning
confidence: 99%
“… 11–14 Next-generation sequencing studies have identified rare germline variants in several other genes, including BRCA2 and many other DNA repair genes. 15–17 …”
Section: Introductionmentioning
confidence: 99%